2018
DOI: 10.1038/s41598-018-19294-1
|View full text |Cite
|
Sign up to set email alerts
|

Treprostinil inhibits proliferation and extracellular matrix deposition by fibroblasts through cAMP activation

Abstract: Idiopathic pulmonary fibrosis (IPF) is characterized by peripheral lung fibrosis and increased interstitial extracellular matrix (ECM) deposition. In IPF, tumor growth factor (TGF)-β1 which is the major stimulus of ECM deposition, and platelet derived growth factor (PDGF)-BB is a potent stimulus of fibrosis. Thus, the effect of Treprostinil on TGF-ß1 and PDGF-induced fibroblast proliferation and ECM deposition was investigated. Human peripheral lung fibroblasts of seven IPF patients and five lung donors were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…Alternatively, our findings in this study and in [18] provide rationale for the use of GPCR agonists of G αs -coupled receptors as treatments that actively trigger YAP/TAZ inactivation and thus will have an antifibrotic potential. This is supported by reports that activating IP receptor by selexipag, treprostinil and iloprost [18,[83][84][85][86][87][88][89], β2-adrenoreceptors by oladaterol [90], or melatonin receptors by melatonin [91] is antifibrotic in vitro and in animal fibrosis models, and at the same time inhibits YAP/TAZ [18,23,91].…”
Section: Discussionsupporting
confidence: 55%
“…Alternatively, our findings in this study and in [18] provide rationale for the use of GPCR agonists of G αs -coupled receptors as treatments that actively trigger YAP/TAZ inactivation and thus will have an antifibrotic potential. This is supported by reports that activating IP receptor by selexipag, treprostinil and iloprost [18,[83][84][85][86][87][88][89], β2-adrenoreceptors by oladaterol [90], or melatonin receptors by melatonin [91] is antifibrotic in vitro and in animal fibrosis models, and at the same time inhibits YAP/TAZ [18,23,91].…”
Section: Discussionsupporting
confidence: 55%
“…Exogenous PDGF-BB is clinically used to treat chronic wounds (4) and facilitates wound healing even in diabetic mice, accompanied by accelerated granulation tissue formation and fibrogenesis (27). PDGF-BB also facilitates ECM production by fibroblasts (28). Furthermore, Pdgfrb deletion diminishes migratory activity, mitotic responses, and cellular survival in dermal fibroblasts (29).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PDGF-BB and its signaling axis are responsible for granulation tissue formation and re-epithelialization (1,3,5). Moreover, PDGF-BB induces a-smooth muscle actin in fibroblasts (28,30), thereby contributing to myofibroblast differentiation. Although our data show that endothelial calpain activity is indispensable for PDGFR-b signaling in wound sites, the mechanisms by which it regulates PDGFR-b signaling are currently unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PGE 2 inhibits the transition of fibroblasts to myofibroblasts [80] and is capable of suppressing fibroblast proliferation and collagen synthesis through EP 2 receptor-mediated pathways [81]. Indeed, anti-fibrotic properties of treprostinil have been reported both in vivo (bleomycin-induced pulmonary fibrotic model) and in vitro (inhibition of TGF-βstimulated collagen production), though the receptor involved was not defined in these studies [82,83]. It should also be mentioned that some of the above effects can be replicated by EP 4 receptors [47,84], suggesting some overlapping function of EP 2 and EP 4 receptors in regulating fibroblast function.…”
Section: Robust Expression Of Ep 2 and Ep 4 Receptors In Pah: Key Antmentioning
confidence: 98%
“…The key question is whether prostanoid drugs used to treat PAH patients have positive effects on vascular remodelling associated with the abnormal proliferation of different cell types within the blood vessel wall. In vitro studies reported from a number of laboratories using vascular cells isolated from the lungs of patients with endstage disease suggest that they should do so in vivo [9,22,83,101]. Our own studies directly comparing the anti-proliferative properties of several clinically approved therapies in PASMCs from PAH patients showed hugely variable responses with the lowest dose to significantly inhibit cell proliferation varying some 10,000-fold from 0.1 nM for treprostinil up to 1 μM for the ET-1 receptor antagonist bosentan [117].…”
Section: Prostacyclin Effects On Vascular Remodelling In Vivo: Outstamentioning
confidence: 99%